Unequal distribution of salary from a gender perspective and the impact of recession on the catalan labor market - M.Jesús Gómez Adillón; M.Àngels Cabasés Piqué (European Regional Science Association (ERSA), 2014)
In order to highlight the uneven impact of recession on the labor market in Catalonia (Spain), especially regarding wage structure, this study examines the evolution of its main variables in the period 2005-2012 from a gender perspective. For ten years prior to recession, female employment improved, mainly due to the expansion of the tertiary sector and public sector and numerous new political and legislative actions. These actions aimed at the interdiction of certain long-held and deep-rooted historical distinctions. These distinctions have not been solved yet for this group: the so called vertical inequalities (concentration of women in lower occupational categories), horizontal (traditionally female occupations) and salary (and lower contribution bases attached to them). We can delve into the structure of wages in Catalonia (Spain) in order to detect and quantify the differences due to gender difference and to analyze the distribution of intergroup and intragroup inequality between men and women. We calculated two measures of inequality such as the Gini index and the Pietra index to quantify the dispersion in the distribution of wages between men and women and for this purpose the model of concentration Kakwani has been adjusted and it has provided a high goodness grip. It is clear that the salary evolution by gender, in the period 2005 - 2012, is different and that it manifests inequalities in the average yearly income despite legislative and social progress in labor matters, which are incorporated in recent years. The conclusions of this study, in line with other studies, confirm that the overall wage dispersion has shown a countercyclical behavior, although, a major incorporation of women with a higher level of education and qualification in the labor market can be observed in the recession period (2005 - 2012). Analyzing the impact of the current recession and quantifying the gender wage inequality between women and men is very important as a framework for effective European action in this area, because is necessary the implementation of positive action in favor of women to correct inequalities, as a smart, sustainable and inclusive growing factor is needed as recommended at European Council of 30 November 2009.
Keywords: E24; J21; J31; 330; labor market; wages; gender inequality